The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1046/j.1529-8817.2003.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex segregation analyses of bone mineral density in Chinese

Abstract: SummaryChina has the largest population in the world; approximately 7% of the total population suffers from primary osteoporosis. Osteoporosis is mainly characterized by low bone mineral density (BMD). In the present study, familial correlation and segregation analyses for spine and hip BMDs have been undertaken for the first time in a Chinese sample composed of 401 nuclear families with a total of 1,260 individuals. The results indicate a major gene of additive inheritance for hip BMD, whereas there is no evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 56 publications
6
17
0
Order By: Relevance
“…This finding is highly consistent with the findings from Chinese family studies [16][17][18] and those from the studies of various Western populations, such as Americans [4,12,14], British [8,15], Icelandics [10], Finns [7,9], Australians [5,6], and Mexican Americans [13]. This consistently high heritability of BMD found all over the various ethnic populations provides strong evidence for the presence of specific genes responsible for BMD and the development of osteoporosis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This finding is highly consistent with the findings from Chinese family studies [16][17][18] and those from the studies of various Western populations, such as Americans [4,12,14], British [8,15], Icelandics [10], Finns [7,9], Australians [5,6], and Mexican Americans [13]. This consistently high heritability of BMD found all over the various ethnic populations provides strong evidence for the presence of specific genes responsible for BMD and the development of osteoporosis.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, heritability of leg BMD was the highest and heritability of arm BMD was the lowest in the whole group of males and females combined. Some studies have reported that lumbar spine BMD had the highest heritability [5,9,17,27], while others have reported that total hip [10,11,14,16,18], femoral neck [8,15], or head [4,7] BMD had the highest heritability. Moreover, the exact mechanism for the different genetic effect on BMD by specific sites is still uncertain.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Liu et al (2004a) reported h 2 estimates of 0.62 for spine bone size and 0.59 for total hip bone size. Other studies reported h 2 estimates of 0.60-0.63 for spine area and 0.45-0.69 for total hip area (Jian et al 2004), and 0.81 for spine BMD and 0.90 for total hip BMD (Liu et al 2004b). The h 2 estimates for trochanter and femoral neck BMD and bone size have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%